2021
DOI: 10.1029/2021gl095159
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Acidification Rates Due to Deposition of Atmospheric Pollutants in the Coastal Bay of Bengal

Abstract: Absorption of atmospheric CO 2 is lowering the pH of surface-ocean at the rate of 0.0015 ± 0.0005 units per year (Bates et al., 2014;Sutton et al., 2017) in the global ocean. The rate of acidification is reported as higher in the coastal than offshore region due to the proximal multiple human activities that modify the carbonate equilibria (e.g., Cai et al., 2011). Deposition of sulfate and nitrate aerosols, formed from fossil fuel and biomass burning, may further decrease pH of surface ocean (Doney et al., 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…Atmospheric dust deposition, the vehicle for AND, directly acidifies the seawater. Nitrification elevated by AND-driven productivity also provides a greater H + concentration in the water column, leading to ocean acidification (negative feedback) (Doney et al, 2007;Sarma et al, 2021). Therefore, AND exerts a combination of positive and negative effects on N 2 O production in STWNPO.…”
Section: Implications For Future Studiesmentioning
confidence: 99%
“…Atmospheric dust deposition, the vehicle for AND, directly acidifies the seawater. Nitrification elevated by AND-driven productivity also provides a greater H + concentration in the water column, leading to ocean acidification (negative feedback) (Doney et al, 2007;Sarma et al, 2021). Therefore, AND exerts a combination of positive and negative effects on N 2 O production in STWNPO.…”
Section: Implications For Future Studiesmentioning
confidence: 99%
“…The lack of primary productivity trends due to an increase in the deposition of nutrients from the atmosphere was reported (Sarma, Prasad, & Dalabehera, 2021; Sridevi et al., 2023). Rapid rate of ocean acidification was reported due to the atmospheric deposition of pollutants (Kumari, Sarma, & Dileep Kumar, 2022; Kumari, Sarma, Mahesh, & Sudheer, 2022; Sarma et al., 2015; Sarma, Krishna, et al., 2021). Therefore, the inclusion of atmospheric pollutants in the model improves the simulations of future changes in CO 2 fluxes significantly.…”
Section: Discussionmentioning
confidence: 99%
“…More recently Sarma et al (2019) reported that cyclonic eddies enhance pCO 2 levels due to upwelling in the core of the eddy while anticyclonic eddies sink for atmospheric CO 2 . Several recent investigations suggested that rapid acidification is being occurred in the BoB due to the deposition of atmospheric pollutants (Kumari, Sarma, & Dileep Kumar, 2022;Kumari, Sarma, Mahesh, & Sudheer, 2022;Sarma et al, 2015;Sarma, Krishna, et al, 2021) leading to an increase in pCO 2 levels. Unfortunately, neither GHM nor RHM has the atmospheric component to consider its impact.…”
Section: Northeastern Indian Ocean (Bay Of Bengal)mentioning
confidence: 99%
See 1 more Smart Citation
“…8,[34][35][36] In addition, efforts have been made to measure the chemical composition of aerosols under the aegis of several national and international programs in India. 13,14,19,23,25,32,[37][38][39][40] Combining several snapshot measurements, Srinivas and Sarin 38 estimated that dry deposition of inorganic nutrients supports $13% of the surface primary production in the Bay of Bengal (BoB) and $5% of the surface primary production in the Arabian Sea (AS) during the dry period. Similarly, Yadav et al 32 highlighted that $70% of the total suspended particulate matter (TSP) was deposited within 10 km from the coast and can support 3 to 33% of the coastal surface primary production during fall and winter seasons in the BoB.…”
Section: Introductionmentioning
confidence: 99%